Diagnosis of Difficulties Faced by Students of Mathematics Education Program at IAIN Lhokseumawe In Understanding Indefinite Integral - Lisa, Lisa; Amin Fauzi, Kms. Muhammad; Sitompul, Pardomuan (Al-Khawarizmi, 2024)
Understanding the concepts and solving problems in the integral calculus course is the problem most often faced by students during the learning process. Therefore, an analysis must be made of the types of learning difficulties faced by students in integral calculus courses, especially indeterminate integrals. The purpose of this research is to identify what problems students face when solving indeterminate integral problems in integral calculus courses. The results are expected to provide an overview of the types of learning challenges faced by students while studying. The type of research used iscase study research with a qualitative approach. The research subjects were 20 students from the second semester of unit 1 of IAIN Lhokseumawe's Tadris Mathematics study programme. The results showed that there were three learning difficulties faced by students, namely Type I (Rigour), Type II (Concept Understanding) and Type III (Calculation Process).